Pengaruh Kebijakan Green Finance terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Mediasi pada Perusahaan Manufaktur Sektor Barang Konsumsi yang Terdaftar di BEI Periode 2022–2024 - Saputra, Imam; Cindiyasari, Shiwi Angelica; Muhammad, Mahatir (Universitas Proklamasi 45, 2025)
This study aims to analyze the impact of green finance policies on the business value of manufacturing companies active in the consumer goods sector and listed on the Indonesia Stock Exchange during the period 2022 to 2024. In this study, profitability is used as an intermediary variable. The analysis was performed using panel data regression and the Sobel test, with support from EViews 12 software. The results show that green finance policies can increase profitability and firm value. Furthermore, the data show that profitability contributes to increasing firm value and acts as a mediator between green finance policies and firm value. This study confirms that green finance improves financial performance and market perception while demonstrating a commitment to environmental sustainability.